PENGARUH CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Kusumawardhani, Indra - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
Abstract This research examine whether corporate governance, ownership structure, firm size affect earnings management on manufacturing companies listed in Indonesian Stock Exchange during 2006-2010. 32 samples obtained with purposive sampling. Results show that corporate governance, ownership structure and firm size simultaneously affected earnings management. Corporate governance and institutional ownership do not partially affect earnings management, while managerial ownership and firm size negatively affect earnings management. Keywords: Corporate Governance, institutional ownership, managerial ownership, firm size, earnings management.